Legal Responsibilities of Foreign Investors in Establishing Unicorn Start-Up Companies in Indonesia (Journal of Private and Commercial Law, 2020)
The flow of globalization is increasing very rapidly and the development of the digital world. Indonesia is one of the countries with the highest e-commerce growth which continues to grow every year, in 2013 internet users were recorded at 72.8 million and in 2016 it became 102.8 million, in 2019 there were 130 million people. PT.PMA needs strict supervision of the financial system including how to collect taxes, considering that the capital invested is not small. A legal system capable of creating certainty, justice, and efficiency as an effort to develop market mechanisms in the era of economic globalization. Without special rules regarding the supervision of foreign investors, of course it will make it difficult for the government to collect taxes and move the financial management system. The aim is to see the responsibilities of foreign investors in managing the financial system in unicorn start-up companies established in Indonesia that are associated with taxation. The research method was carried out normative-empirical which was presented in a qualitative descriptive. Some company investors in start-up companies come as a whole from domestic investors and some even use foreign investors to intervene. Article 5 paragraph (2) of the Company Law states that foreign investment in Indonesia must be in the form of a Limited Liability Company (PT) based on Indonesian law and the government in this case is not allowed to grant â€œspecial rightsâ€ to treatment of a country. Start-up companies, both foreign and domestic, must pay taxes in accordance with the provisions imposed in Indonesia. With the implementation of this tax, it has resulted in an increase in state profits. Apart from affirming the obligation of investors to pay taxes, the principles of sound corporate governance are embodied, respecting the cultural traditions of the community, and implementing corporate social responsibility